2018
DOI: 10.1016/j.immuni.2018.04.029
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Vaccines Based on Antibody Identification, B Cell Ontogeny, and Epitope Structure

Abstract: HIV-1 vaccine development has been stymied by an inability to induce broadly reactive neutralizing antibodies to the envelope (Env) trimer, the sole viral antigen on the virion surface. Antibodies isolated from HIV-1-infected donors, however, have been shown to recognize all major exposed regions of the prefusion-closed Env trimer, and an emerging understanding of the immunological and structural characteristics of these antibodies and the epitopes they recognize is enabling new approaches to vaccine design. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
316
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(321 citation statements)
references
References 198 publications
(338 reference statements)
5
316
0
Order By: Relevance
“…For HIV-1, the discovery of broadly neutralizing antibodies (bnAbs) that protect against infection across diverse viral isolates has intensified efforts to understand the developmental pathway of the rare B cells that produce these antibodies (6)(7)(8)(9). Insights into the ontogeny of these rare B cells could allow the design of a step-wise vaccine regimen that stimulates the germ-line precursor to expand and mature to produce circulating bnAbs which could protect against HIV acquisition (10,11). For RSV, stabilized versions of the fusion (F) protein in the pre-fusion conformation have led to insights in the B cell's response to infection and has generated potentially safer and more efficacious vaccine candidates (12,13).…”
Section: Why Study B Cell Responses? Opportunities For Applying Technmentioning
confidence: 99%
“…For HIV-1, the discovery of broadly neutralizing antibodies (bnAbs) that protect against infection across diverse viral isolates has intensified efforts to understand the developmental pathway of the rare B cells that produce these antibodies (6)(7)(8)(9). Insights into the ontogeny of these rare B cells could allow the design of a step-wise vaccine regimen that stimulates the germ-line precursor to expand and mature to produce circulating bnAbs which could protect against HIV acquisition (10,11). For RSV, stabilized versions of the fusion (F) protein in the pre-fusion conformation have led to insights in the B cell's response to infection and has generated potentially safer and more efficacious vaccine candidates (12,13).…”
Section: Why Study B Cell Responses? Opportunities For Applying Technmentioning
confidence: 99%
“…Among the bnAbs isolated to date, those targeting the CD4bs are the most abundant and thoroughly studied as they disrupt the first and crucial step of viral interaction with the cellular receptor CD4 [3,4,17,18]. In this step, the trimeric envelope glycoprotein, composed of gp120 and gp41, binds with the target cell through the receptor CD4, with either CCR5 or CXCR4 as co-receptor [19][20][21].…”
Section: Author Summarymentioning
confidence: 99%
“…Resistance is largely attributed to mutated residues within the epitopes or steric hindrance imposed by the bulky side-chain or glycan shield of the mutated residues, and is largely correlated with reduced binding avidity of the antibody to the quaternary trimeric envelope protein expressed on the PLOS Pathogens | https://doi.surface of the transfected cells. Treatment strategies based on the CD4bs bnAbs therefore must overcome such resistance to achieve optimal clinical outcomes.Recent scientific advances have identified a growing number of broadly neutralizing antibodies (bnAbs) against human immunodeficiency virus type I (HIV-1), providing promising candidates for HIV-1 prevention and treatment [1][2][3][4][5]. Compared with bnAbs isolated in earlier studies, these bnAbs demonstrated broader and more potent activity against global HIV-1 panels and displayed impressive safety and efficacy profiles for therapeutic applications in a number of animal models and human clinical trials [1,[6][7][8][9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Antigenic mismatch between vaccine and circulating strains impacted vaccine efficacy (Juraska et al, 2018), highlighting the importance of rational selection of vaccine components. An alternative strategy, largely exemplified by vaccine development efforts for HIV (Kwong & Mascola, 2018) and respiratory syncytial virus (RSV) (Crank et al, 2019), relies on identifying antibodies with desirable properties and precisely defining their epitopes to guide epitope-based vaccine design (Graham, Gilman, & McLellan, 2019). For antigenically diverse viruses such as DENV, a conserved epitope-based vaccine strategy to elicit a broad and potent monoclonal neutralizing antibody response could mitigate the challenge of selecting representative vaccine strains.…”
Section: Introductionmentioning
confidence: 99%